2021
DOI: 10.21203/rs.3.rs-330571/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Yak Dung Seed Bank on the Qinghai-Tibetan Plateau: Effects of Grazing Season, Seed Characteristics and Forage Preferences

Abstract: AimsViable seeds in herbivore dung constitute the dung seed bank, and the contribution of livestock dung to this seed bank in grazing pastures is often overlooked. Grazing season (warm and cold), seed characteristics (mass and shape), and forage preference are the main factors that affect the size and composition of the dung seed bank and ultimately affect grassland ecology. However, how these three factors interact is unclear. Methodswe collected yak dung as well as seeds of the common plant species from warm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Wang et al (2019) found that the relationship between the tan sheep DSB and AGV was weak on the Loess Plateau of China. The present study showed a high dissimilarity between the DSB for each of the three livestock species and the AGV during the 3-year experimental period (Figure 5), indicating that the DSB had the potential to increase the heterogeneity of the AGV near the microsites of the dung pieces (Wang & Hou, 2021b;Yu, Xu, Muhammad, & Long, 2013). Meanwhile, the livestock has long gut retention times and can move several kilometres every day (Manzano et al, 2005; F I G U R E 4 Dung seedling density (seedlings g À1 dung), richness and diversity among livestock species during 2018-2020.…”
Section: Comparison Of the Dsb And Agvmentioning
confidence: 66%
See 2 more Smart Citations
“…Wang et al (2019) found that the relationship between the tan sheep DSB and AGV was weak on the Loess Plateau of China. The present study showed a high dissimilarity between the DSB for each of the three livestock species and the AGV during the 3-year experimental period (Figure 5), indicating that the DSB had the potential to increase the heterogeneity of the AGV near the microsites of the dung pieces (Wang & Hou, 2021b;Yu, Xu, Muhammad, & Long, 2013). Meanwhile, the livestock has long gut retention times and can move several kilometres every day (Manzano et al, 2005; F I G U R E 4 Dung seedling density (seedlings g À1 dung), richness and diversity among livestock species during 2018-2020.…”
Section: Comparison Of the Dsb And Agvmentioning
confidence: 66%
“…For example, in grazing ecosystems, because of livestock feeding preferences, a large number of plant seeds accumulate in faeces (the 'fertile island effect') (Cai et al, 2020). The heterogeneity in the composition between the DSB and that of AGV indicates that the DSB is a potential driving force for the formation of grassland patching due to grazing (Fulgoni et al, 2020;Wang & Hou, 2021a, 2021bYu et al, 2012;Yu, Xu, Wang, Shang, & Long, 2013). Moreover, in arid environments such as the desert grassland of the study site, seed dispersal via dung pellets provides substantial protection for seeds until sufficient rainfall occurs to allow germination and seedling establishment, thus representing an adaptation for survival in this type of harsh environment.…”
Section: Comparison Of the Dsb And Agvmentioning
confidence: 99%
See 1 more Smart Citation
“…These viable seeds in herbivore feces constitute the dung seed bank (DSB; Wang & Hou, 2021;Wang, Hu, et al, 2019), which defined as a subset of the SSB and is an important source of vegetation renewal. The structure of the DSB depends on rangeland composition and selective feeding by livestock (Wang & Hou, 2021). The DSB is a special form of the SSB, as once dung decomposes, seeds in the feces are eventually incorporated into the soil, contributing to the SSB.…”
mentioning
confidence: 99%
“…When mature plant seeds are consumed by foraging livestock, some of these seeds survive passage through the digestive tract and are ultimately deposited in dung. These viable seeds in herbivore feces constitute the dung seed bank (DSB; Wang & Hou, 2021;Wang, Hu, et al, 2019), which defined as a subset of the SSB and is an important source of vegetation renewal. The structure of the DSB depends on rangeland composition and selective feeding by livestock (Wang & Hou, 2021).…”
mentioning
confidence: 99%